Two-stroke engine control (2022)
A two-stroke combustion engine comprising a user-operated throttle control, an adjustable valve arranged to control one or more air intakes of the combustion engine, and a control unit arranged to control a state of the adjustable valve, wherein the combustion engine is arranged to operate in a first idle mode at an idle engine speed below a clutch engagement engine speed when the user-operated throttle control is not engaged, wherein the combustion engine is arranged to operate in a second idle mode at a target engine speed above the clutch engagement engine speed when the user-operated throttle control is engaged and when the engine is not subject to an external load, the control unit being arranged to control the state of the adjustable valve to maintain engine speed at the target engine speed when the engine operates in the second idle mode.